Population fluctuation of Aceria annonae (Keifer, 1973) (Prostigmata: Eriophyidae), in three municipalities of Nayarit, Mexico - Flores-Canales, Ricardo Javier; Acuña-Soto, Jesús Alberto; Santillán-Ortega, Candelario; Isiordia-Aquino, Néstor; Sotelo-Montoya, Anacelia Miroslava; Hernández-Zaragoza, Ricardo Daniel (Revista Mexicana de Ciencias Agrícolas, 2019)
Nayarit is the main producer of soursop (Annona muricata L.) worldwide. Among the main limitations for production are mites, so, in order to know the population fluctuation of the eriophyid Acerio annonae (Keifer) between February and December 2016, periodic sampling was done every 30 days in three municipalities and four localities: Compostela (Altavista and El Divisadero), Xalisco (San Antonio) and Tepic (El Trapichillo). For the samplings, 10 trees were considered by location, randomly selected; each tree was divided into five sampling areas, one per cardinal point, with one leaf (sample) per area, also randomly selected, for a total of 50 samples per location. The samples were taken to the agricultural parasitology laboratory of the Agricultural Academic Unit at the Autonomous University of Nayarit, where the total number of adults and adults per sheet was periodically quantified from each locality. The variables number of erineos by leaf, number of adults by erineos and the climatic factors, were correlated by means of the correlation coefficient of Pearson (SAS Institute, 2004). Of the four localities only positive correlation was obtained in the locality of San Antonio, where the temperature seems to have an effect on the variables of erineos per leaf (CC= 0.89885 and Prob> |R|= 0.0002) and adults by erineo (CC= 0.62875 and Prob> |R|= 0.0385), for the locality of El Trapichillo, only the variable erineos per leaf was correlated with the temperature with the number of erineos per leaf, (CC= 0.85937 and Prob> |R|= 0.0007).